A road less travelled? The Society for Libyan Studies and the landscape archaeology of Libya's early civilisations. (November 2019) - Mattingly, David J.
Abstract: This contribution explores a key dimension of the work of the Society for Libyan Studies concerning the archaeology of Libya's Protohistoric and early historic periods (broadly first millennium BC and first millennium AD). This primarily concerns the archaeology of rural landscapes (including the desert) and the investigation of the ancient Libyan populations that inhabited them. Taking an autobiographical approach, I review the contributions to developing research agendas made by a number of research projects that I have been involved in. The results collectively have advanced knowledge and understanding not only of this aspect of ancient Libyan society, but also have important implications for the construction of Libyan identity and the management of its heritage today. More broadly, they constitute an important contribution to wider re-evaluation of Maghribian and Saharan societies in the Iron Age and Roman periods. Abstract : الطريق الأقل سفراً؟ جمعية الدراسات الليبية و المشهد الأثري للحضارات المبكرة في ليبيا. بقلم ديفيد ماتينجلي تستكشف هذه المساهمة بعداً رئيسياً من أعمال جمعية الدراسات الليبية فيما يتعلق بآثار فترات ما قبل التاريخ و أوائل الاحقاب التاريخية الليبية (في نطاق واسع الألفية الأولى قبل الميلاد والألفية الأولى بعد الميلاد). يتعلق هذا في المقام الأول بآثار المشهد الريفي (بما في ذلك الصحراء) و دراسة الليبيين القدماء الذين سكنوا فيه. باتباع نهج السيرة الذاتية (autobiographical) ، أراجع المساهمات في تطور برامج البحوث التي قدمتها عدد من المشاريع البحثية و التي شاركت فيها. والنتائج مجتمعة أسهمت في تقدم المعرفة و الفهم ليس فقط لهذا الجانب من المجتمع الليبي القديم، ولكن كان لها أيضاً التأثير المهم في بناء الهوية الليبية و إدارة تراثها اليوم. على نطاق أوسع، فإنها تشكل مساهمة مهمة في إعادة تقييم أكبر للمجتمعات المغاربية والصحراوية في العصر الحديدي والعصور الرومانية.